IMPLEMENTATION TEACHING CAMPUS PROGRAM ACTIVITIES (KAMPUS MENGAJAR) ON STUDENTS LEARNING EFFECTIVENESS IN SD NEGERI 1 MEMBALONG BELITUNG - Taufiqulloh Dahlan; Junaidi Junaidi; Zulkifli Zulkifli; Amila Amila; Indri Puspita; Jeany Arsy Maqin; Rata Bila Bagi; Tiara Roza (Pasundan International of Community Services Journal (PICS-J), 2021)
This study aims to examine the effect of teaching program activities to see the effectiveness of student learning at SD Negeri 1 Membalong. During the COVID-19 pandemic, teaching and learning activities were shifted to face-to-face learning. Students learn by using various features provided on the internet. For approximately 1 year studying at home, over time now several schools have implemented a new normal and have carried out face-to-face learning activities, one of which is at SD Negeri 1 Membalong while still paying attention to health protocols. Campus teaching program activities are one of the activities that help teachers in teaching and learning activities, administration and introduction of technology. This campus teaching activity is a program designed by Nadiem Makarim which involves students going directly to schools located in 3T areas (frontier, outermost, remote). This activity has a positive impact on students and schools involved in this activity. The purpose of this article is to see how influential this teaching activity program is, then examine how effectively students study at SD Negeri 1 Membalong during the pandemic. This study uses an interactive qualitative method with complete data collection using observations, interviews and documentation during activities at SD Negeri 1 Membalong.